Benzyl butyl phthalate (BBP) triggers the migration and invasion of hemangioma cells via upregulation of Zeb1. (October 2019) - Cui, Shuo; Wang, Linlei; Zhao, Huafei; Lu, Fei; Wang, Weixin; Yuan, Zhengjiang
Abstract: Hemangioma (HA) are tumors formed by hyper-proliferation of vascular endothelial cells. As a potential endocrine disrupting chemical (EDC), benzyl butyl phthalate (BBP) can mimic estrogen to disturb the estrogenic signals. Our present study investigated the potential roles of phthalates on the progression of HA and found that 100 nM BBP can significantly trigger the migration and invasion of HA cells, which was evidenced by the results that BBP can induce the expression of matrix metalloproteinase (MMPs) and vimentin. Further, BBP can increase the expression of Zeb1, one powerful transcription factor for cell migration and invasion. Targeted inhibition of Zeb1 blocked BBP induced cell migration. Mechanistically, BBP can increase the mRNA stability of Zeb1 via suppression of miR-655. Further, BBP can enhance the protein stability of Zeb1 via upregulation of ataxia telangiectasia mutated (ATM). Collectively, our present study revealed that BBP can trigger the migration and invasion of HA cells via upregulation of Zeb1. Highlights: BBP triggers the motility of HA cells. Zeb1 is involved in BBP induced cell motility. miR-655 is involved in BBP increased mRNA stability of Zeb1. TAM mediates BBP increased protein stability of Zeb1.